2020
DOI: 10.2147/ppa.s245623
|View full text |Cite
|
Sign up to set email alerts
|

<p>Patient Attitudes to Routine Cognitive Testing in Multiple Sclerosis</p>

Abstract: Background and Aim: In recent years, cognitive dysfunction (CD) in multiple sclerosis (MS) has received increased attention. Neuropsychological tests have been developed allowing to monitor changes in patients' cognitive functions. Knowledge is lacking, however, about patients' attitudes towards introducing routine cognitive testing. It was the aim of this qualitative study to explore this. Materials and Methods: Based on a literature study, semi-structured interview guides were designed and used in qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Like in Mortensen et al (2020), we found that routine cognitive screening was seen as valuable for both people with MS and clinicians. Both and subjective cognitive assessments were viewed as appropriate.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Like in Mortensen et al (2020), we found that routine cognitive screening was seen as valuable for both people with MS and clinicians. Both and subjective cognitive assessments were viewed as appropriate.…”
Section: Discussionmentioning
confidence: 57%
“…However, few studies have qualitatively evaluated 'how' specific tests or batteries are used. An investigation into patient preference for routine cognitive screening found the people with MS were supportive of routine cognitive screening and for their clinicians to manage both physical and cognitive symptoms (Mortensen et al, 2020). Participants perceived the SDMT to be less demanding and fatiguing than the other brief assessments included in the BICAMS (Brief International Cognitive Assessment for MS).…”
Section: Introductionmentioning
confidence: 99%
“…The sources of information that currently exist for PwMS may not adequately address cognition in an accessible way. Qualitative studies have also demonstrated that PwMS want cognition information at diagnosis and feel that documentation of their cognitive difficulties would facilitate communication about their situation with others (Mortensen et al, 2020). PwMS increasingly expect to be fully involved in shared decision making and to be given comprehensive, current information (Yeandle et al, 2018).…”
Section: (I) Informationmentioning
confidence: 99%
“…This finding is consistent with previous research that shows that cognitive symptoms can be under‐emphasized in the clinical assessment of MS (Nabavi & Sangelaji, 2015). In the present study, all participants wanted routine assessment and monitoring of their communication skills, which may help to optimize management, enhance the individual's quality of life, and document and raise awareness of this invisible symptom (Mortensen et al., 2020; Nabavi & Sangelaji, 2015). Previous research has shown that PwMS have positive attitudes towards and endorse routine cognitive testing (Mortensen et al., 2020), which was confirmed here.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, all participants wanted routine assessment and monitoring of their communication skills, which may help to optimize management, enhance the individual's quality of life, and document and raise awareness of this invisible symptom (Mortensen et al., 2020; Nabavi & Sangelaji, 2015). Previous research has shown that PwMS have positive attitudes towards and endorse routine cognitive testing (Mortensen et al., 2020), which was confirmed here. Baseline and annual screening, and baseline and periodic neuropsychology assessment has been recommended by a multidisciplinary expert panel, particularly in the presence of subjective complaints, positive screening scores or specific social or work situations (Meca‐Lallana et al., 2021).…”
Section: Discussionmentioning
confidence: 99%